New cages and unusual guests: Fullerene chemistry continues to excite - Hirsch, Andreas (Angewandte Chemie International Edition, 2001)
Minifullerenes, bizarre cages, and highly reactive guests are currently causing a stir in fullerene chemistry. An example is C, recently generated in the gas phase, which constitutes the smallest conceivable classical fullerene.